2020
DOI: 10.1021/acs.organomet.0c00518
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Molybdenum Hydrido(hydrogermylene) Complex and Its Conversion to a Germylyne Complex: Another Route through Dehydrogenation with Nitriles

Abstract: A molybdenum germylene complex having Mo−H and Ge−H bonds, Cp*(CO) 2 (H)MoGe(H){C(SiMe 3 ) 3 } (1), was synthesized by the reaction of a methyl molybdenum complex with a trihydrogermane and was converted to a germylyne complex, Cp*(CO) 2 MoGe{C(SiMe 3 ) 3 } (2), via dehydrogenation with aryl isocyanates under mild heating. A similar conversion from the same germylene complex into the germylyne complex also occurred using nitriles instead of isocyanates, while releasing imines via a Mo−Ge−N three-membered rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 46 publications
4
28
0
Order By: Relevance
“…20 The SC-XRD study revealed that both complexes 10a/b have very short MGe bonds and have linear geometries as indicated by their MGeC(substituent) angles (172173°). 20,21 Very recently, our group also found that similar dehydrogenation occurred using nitriles instead of arylisocyanates in the molybdenum system (Scheme 7). 21 In this case, three-memberedring intermediates Cp*(CO) 2 Mo[¬ 2 (N,Ge)-Ge(H)(N=CHR)(Tsi)] (12) were formed via CÔN hydrogermylation of nitriles and converted to germylyne complex 10b with releasing imines.…”
Section: Germylyne (Or Germylidyne) Complexesmentioning
confidence: 89%
See 3 more Smart Citations
“…20 The SC-XRD study revealed that both complexes 10a/b have very short MGe bonds and have linear geometries as indicated by their MGeC(substituent) angles (172173°). 20,21 Very recently, our group also found that similar dehydrogenation occurred using nitriles instead of arylisocyanates in the molybdenum system (Scheme 7). 21 In this case, three-memberedring intermediates Cp*(CO) 2 Mo[¬ 2 (N,Ge)-Ge(H)(N=CHR)(Tsi)] (12) were formed via CÔN hydrogermylation of nitriles and converted to germylyne complex 10b with releasing imines.…”
Section: Germylyne (Or Germylidyne) Complexesmentioning
confidence: 89%
“…20,21 Very recently, our group also found that similar dehydrogenation occurred using nitriles instead of arylisocyanates in the molybdenum system (Scheme 7). 21 In this case, three-memberedring intermediates Cp*(CO) 2 Mo[¬ 2 (N,Ge)-Ge(H)(N=CHR)(Tsi)] (12) were formed via CÔN hydrogermylation of nitriles and converted to germylyne complex 10b with releasing imines. Notably, when arylnitriles were employed, the corresponding conversion was enhanced by LED light irradiation.…”
Section: Germylyne (Or Germylidyne) Complexesmentioning
confidence: 89%
See 2 more Smart Citations
“…[1][2][3] In this regard, heavier tetrylenes (:ER2; E = Si, Ge, Sn, Pb) offer unique opportunities as single-site ambiphiles (σ-donating lone pair and empty p orbital), revealing unusual coordination modes and reactivity. [4][5][6][7][8][9][10][11][12] Moreover, they represent the prospects of new avenues for transition metal/P-element cooperation. [13][14][15][16][17][18][19][20][21][22][23][24][25] However, the coordination chemistry of tetrylenes remains considerably less explored than their lighter carbene congeners, in no little part due to reduced stability.…”
mentioning
confidence: 99%